The Essentials of Management : Everything you need to succeed as a new manager - Leigh, Andrew, author 333111 (New York : Pearson, 2012)
Distilling years of hard-won success, experience, lessons and management wisdom, this book will help new and aspiring managers be the best they can be. For new and aspiring managers this exciting book will enable you to quickly learn all the clever and powerful tips, tricks, advice andknow-how that seasoned and experienced managers already know.You will pick up effective ideas and learn powerful, practical skills that will help you become a better, more successful manager who really delivers results.